2016
DOI: 10.1021/acs.nanolett.6b03409
|View full text |Cite
|
Sign up to set email alerts
|

Near-Atomic Three-Dimensional Mapping for Site-Specific Chemistry of ‘Superbugs’

Abstract: Emergence of multi-drug resistant Gram-negative bacteria has caused a global health crisis and last-line class of antibiotics such as polymyxins are increasingly used. The chemical composition at the cell surface plays a key role in antibiotic resistance. Unlike imaging the cellular ultrastructure with well-developed electron microscopy, acquisition of a high-resolution chemical map of the bacterial surface still remains a technological challenge. In this study, we developed an atom probe tomography (APT) anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 32 publications
(80 reference statements)
1
31
0
Order By: Relevance
“…Knowledge acquired by various high‐resolution imaging techniques including (cryo‐)electron microscopy, confocal imaging, and secondary ion mass spectrometry (SIMS) has contributed to a fundamental understanding of cell biology as well as the engineered development of biomimetic materials with new physical and chemical properties . Atom probe tomography (APT), the only technique offering 3D chemical measurements with near atomic resolution, has recently demonstrated its unique capability as a biological imaging tool to mammalian and bacterial cells …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Knowledge acquired by various high‐resolution imaging techniques including (cryo‐)electron microscopy, confocal imaging, and secondary ion mass spectrometry (SIMS) has contributed to a fundamental understanding of cell biology as well as the engineered development of biomimetic materials with new physical and chemical properties . Atom probe tomography (APT), the only technique offering 3D chemical measurements with near atomic resolution, has recently demonstrated its unique capability as a biological imaging tool to mammalian and bacterial cells …”
Section: Introductionmentioning
confidence: 99%
“…Organic materials, however, are more sensitive to the application of a laser due to the possibility of thermally induced phase transition of the constituent molecules during the field evaporation process . In previous studies, it has been demonstrated that a thin layer of conductive metal coated on an APT specimen can help fulfil the required voltage distribution for field evaporation of nonconductive materials . This physical vapor deposition (PVD) based approach, however, also demonstrated limitations to achieve ultrathin coating of high‐aspect ratio geometries, i.e., tip specimens for APT .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specimen fracture and field-induced deformation has therefore, to date, largely precluded routine atom probe analysis of soft materials. [15] Notable exceptions include studies of ferritin clusters [16] and molecules, [17,18] mammalian and bacterial cells, [19,20] and organic fibers in the chiton tooth. [21] In the present work, we used a sol-gel method to embed rabbit immunoglobulin G (IgG) [22] in a solid silica matrix.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated near-atomic resolution of chemically-resolved data of bulk bio-mineralized hard biological matter such as teeth and bone [45][46][47][48][49][50][51] . Progress was also made on more soft materials such as cells 52,53 and also with ferritin as example for proteins [54][55][56] . In early designs of the atom probe microscope, single amino acids, nucleic acids and other polymers were successfully analyzed [57][58][59][60] .…”
Section: Introductionmentioning
confidence: 99%